Does telling white lies signal pro-social preferences? - Laura Biziou-van-Pol; Jana Haenen; Arianna Novaro; Andrés Occhipinti Liberman; Valerio Capraro (Judgment and Decision Making, 2015)
The opportunity to tell a white lie (i.e., a lie that benefits another person) generates a moral conflict between two opposite moral dictates, one pushing towards telling the truth always and the other pushing towards helping others. Here we study how people resolve this moral conflict. What does telling a white lie signal about a person’s pro-social tendencies? To answer this question, we conducted a two-stage 2x2 experiment. In the first stage, we used a Deception Game to measure aversion to telling a Pareto white lie (i.e., a lie that helps both the liar and the listener), and aversion to telling an altruistic white lie (i.e., a lie that helps the listener at the expense of the liar). In the second stage we measured altruistic tendencies using a Dictator Game and cooperative tendencies using a Prisoner’s dilemma. We found three major results: (i) both altruism and cooperation are positively correlated with aversion to telling a Pareto white lie; (ii) both altruism and cooperation are negatively correlated with aversion to telling an altruistic white lie; (iii) men are more likely than women to tell an altruistic white lie, but not to tell a Pareto white lie. Our results shed light on the moral conflict between prosociality and truth-telling. In particular, the first finding suggests that a significant proportion of people have non-distributional notions of what the right thing to do is, irrespective of the economic consequences, they tell the truth, they cooperate, they share their money.